Aktivitas Penghambatan Ekstrak Etanol Daun Cassia Spectabilis Terhadap Pertumbuhan Plasmodium falciparum dan Plasmodium berghei - Wiwied Ekasari; Nindya Tresiana; Suciati Iryani; Tutik Sri Wahyuni; Heny Arwaty (Universitas Airlangga, 2016)
Background: Antimalarial screening against nine species of the genus Cassia showed that the methanol extract of leaves Cassia spectabilis have the highest activity. Since it will be used as a traditional medicine, hence it is needed further studies of antimalarial activity of these plants by choosing a safer solvent, namely ethanol. Objective: In vitro anti-malarial activity against Plasmodium falciparum was conducted using the method of Trager and Jensen. Methods: The serial solution tested were: 100, 10, 1, 0.1 and 0.01 µg/ mL, while the in vivo test was performed based on Peter's test (The days suppressive test) that using P. berghei (strain ANKA) infected mice. Results: The results showed that ethanolic extract of C. spectabilis leaves has inhibitory activity against P. falciparum with IC50 value of 12.52 µg/ mL and against P. berghei with ED50 value of 131.5 mg/kg body weight. Conclusions: A further study to see the potential of ethanol extract from C. Spectabilis leaves as anti-malaria is warranted.